Dinamika Kehidupan Pasien Terminal Illness Di Rumah Sakit HKBP Balige - Sagala, Erika Dona; Sitanggang, Radesman; Malau, Diana Christiany (Sekolah Tinggi Diakones HKBP, 2023)
Terminal illness is a patient's condition that has reached the chronic stage and the doctor's diagnosis states that the patient can no longer recover. In reality, many terminal illness patients try to recover through the treatment process they follow. This research aims to discover the description and lives of terminal illness patients at the HKBP Hospital Balige and the factors that influence their lives. By using descriptive type qualitative research methods, it was found that the dynamics of the lives of terminal illness patients were at a fragile stage. A weak self-condition brings feelings of sadness and fear of death. There are two factors that influence the dynamics of the lives of terminal illness patients, namely internal factors, namely the decline in body quality and external influences of support from the family environment, community and relationship with God. The impact of pastoral care on the dynamics of life of terminal illness patients is a positive impact, patients are able to express their feelings. The negative impact is that patients have not accepted the conditions for traditional treatment and rarely receive medical treatment.